EFFECT OF LIQUIDITY RATIO AND SOLVENCY RATIO ON STOCK PRICES IN PT KALBE FARMA TBK - Lisdawati Lisdawati; Endang Nurita; Akhmad Akbar (Yayasan Education and Social Center, 2022)
This study is entitled “Effect of Liquidity Ratio and Solvency on Stock Prices in PT Kalbe Farma TBK.